2018
DOI: 10.3389/fphys.2018.00813
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin-2 Prevents Dysregulation of Ca2+ Homeostasis and Improves Early Cardiac Remodeling After Ischemia and Reperfusion

Abstract: Aims: Urocortin-2 (Ucn-2) is a potent cardioprotector against Ischemia and Reperfusion (I/R) injuries. However, little is known about its role in the regulation of intracellular Ca2+ concentration ([Ca2+]i) under I/R. Here, we examined whether the addition of Ucn-2 in reperfusion promotes cardioprotection focusing on ([Ca2+]i handling.Methods and Results: Cardiac Wistar rat model of I/R was induced by transient ligation of the left coronary artery and experiments were conducted 1 week after surgery in tissue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 45 publications
(53 reference statements)
1
47
0
Order By: Relevance
“…Since it is known that the activation of TRPC channels mediates the Ca 2+ influx which in post-MI heart damages. Cardiac hypertrophy is also observed in rat heart tissue as early as 1 week post-I/R, which correlates with the upregulation of the expression of TRPC1, 3, 4, 5 and 6 mRNA [13] and the activation of the so-called fetal gene program, the markers of cardiac hypertrophy (unpublished data). Recently, Dragún et al [104] [13].…”
Section: Trpc Channels In Early Adaptative Cardiac Remodelingmentioning
confidence: 77%
See 3 more Smart Citations
“…Since it is known that the activation of TRPC channels mediates the Ca 2+ influx which in post-MI heart damages. Cardiac hypertrophy is also observed in rat heart tissue as early as 1 week post-I/R, which correlates with the upregulation of the expression of TRPC1, 3, 4, 5 and 6 mRNA [13] and the activation of the so-called fetal gene program, the markers of cardiac hypertrophy (unpublished data). Recently, Dragún et al [104] [13].…”
Section: Trpc Channels In Early Adaptative Cardiac Remodelingmentioning
confidence: 77%
“…In human cardiac tissues and/or neonatal rat cardiomyocytes mRNA of TRPC5 [20,21] and TRPC6 [22] were detected. In animal model, the expression of TRPC1/3-7 have been confirmed in adult rat and mouse ventricle and atrial cardiac myocytes either at mRNA or protein levels [13,23,24]. Others reports showed that TRPC1/3-6 are expressed in rat ventricular myocytes of fetal and neonatal ventricular myocytes [19,25].…”
Section: Trpc Channels In the Cardiovascular Systemmentioning
confidence: 95%
See 2 more Smart Citations
“…Notably, TRPC1 channels are believed to mediate the non-selective cation current and to form SOC channels as a component in human atria [63], in the mouse sinoatrial node [64], in human cardiac c-kit+ progenitor cells [65], in NRVMs [66], and in adult ventricular cardiomyocytes [36,46,67]. Similarly, TRPC5, which was found to contribute to the formation of SOCE in smooth muscle cells isolated from rabbit pial arterioles [68], contributes to SOCE in NRVMs [11,69]. In addition, STIM1, the critical constituent of SOCE, can directly bind to and activate TRPC1 and TRPC5 channels via interactions in its ezrin/radixin/moesin (ERM) domain [70][71][72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 99%